New directions in the anthropology of dreaming
1 online resource (xi, 238 pages)
Keywords: "This book presents new directions in contemporary anthropological dream research, surveying recent theorizations of dreaming that are developing both in and outside of anthropology. It incorporates new findings in neuroscience and philosophy of mind while demonstrating that dreams emerge from and comment on sociohistorical and cultural contexts. The chapters are written by prominent anthropologists working at the intersection of culture and consciousness who conduct ethnographic research in a variety of settings around the world, reflecting how dreaming is investigated with a range of informants in ever more diverse sites. As well as theorizing the dream in light of current anthropological and psychological research, the volume accounts for local dream theories and how they are situated within distinct cultural ontologies. It considers dreams as a resource for investigating and understanding cultural change, dreaming as a mode of thinking through, contesting, altering, consolidating, or escaping from identity, and the nature of dream mentation. In proposing new theoretical approaches to dreaming, the editors situate the topic within the recent call for an "anthropology of the night" and illustrate how dreams offers insight into current debates within anthropology's mainstream. This up-to-date book defines a twenty-first century approach to culture and the dream that will be relevant to scholars from anthropology as well as other disciplines such as religious studies, the neurosciences, and psychology"--